2006
DOI: 10.5194/acpd-6-7563-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution, magnitudes, reactivities, ratios and diurnal patterns of volatile organic compounds in the Valley of Mexico during the MCMA 2002 and 2003 field campaigns

Abstract: Abstract. A wide array of volatile organic compound (VOC) measurements was conducted in the Valley of Mexico during the MCMA-2002 and 2003 field campaigns. Study sites included locations in the urban core, in a heavily industrial area and at boundary sites in rural landscapes. In addition, a novel mobile-laboratory-based conditional sampling method was used to collect samples dominated by fresh on-road vehicle exhaust to identify those VOCs whose ambient concentrations were primarily due to vehicle emissions. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
119
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(139 citation statements)
references
References 38 publications
19
119
1
Order By: Relevance
“…Other possible reasons for the difference include different estimations of VOC emissions and different meteorological conditions during the simulated events. It has also been suggested that vertical mixing is too rapid in the CIT model used here (Velasco et al, 2007), which can also lead to a more NO x -sensitive simulation, but report good agreement with NO y measurements, suggesting that errors in vertical mixing may not be large. West et al (2004) and Lei et al (2007) Lei et al were also supported by measurement-based analyses, although with some uncertainty (Velasco et al, 2005(Velasco et al, , 2007.…”
Section: Implications For Ozone-precursor Sensitivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Other possible reasons for the difference include different estimations of VOC emissions and different meteorological conditions during the simulated events. It has also been suggested that vertical mixing is too rapid in the CIT model used here (Velasco et al, 2007), which can also lead to a more NO x -sensitive simulation, but report good agreement with NO y measurements, suggesting that errors in vertical mixing may not be large. West et al (2004) and Lei et al (2007) Lei et al were also supported by measurement-based analyses, although with some uncertainty (Velasco et al, 2005(Velasco et al, , 2007.…”
Section: Implications For Ozone-precursor Sensitivitymentioning
confidence: 95%
“…It has also been suggested that vertical mixing is too rapid in the CIT model used here (Velasco et al, 2007), which can also lead to a more NO x -sensitive simulation, but report good agreement with NO y measurements, suggesting that errors in vertical mixing may not be large. West et al (2004) and Lei et al (2007) Lei et al were also supported by measurement-based analyses, although with some uncertainty (Velasco et al, 2005(Velasco et al, , 2007. It is also possible that the different emissions adjustments used by West et al andLei et al reflect reductions in ambient VOC between 1997 and.…”
Section: Implications For Ozone-precursor Sensitivitymentioning
confidence: 95%
“…Jimenez et al (2003) demonstrated that the spatial and temporal distribution of CO and NO x follows that of the traffic, while Pfeffer (1994) and Perrino et al (2002) showed that the mean concentrations of gaseous pollutants at very busy junctions are considerably higher than those of areas that are not directly affected by road traffic. Ambient NMVOC levels are mainly affected by motor vehicle emissions where high levels of aromatic hydrocarbons (toluene, benzene and xylenes) have been detected and associated with diverse public transport systems (Velasco et al, 2007; …”
Section: Urban Scalementioning
confidence: 99%
“…More recently, Velasco et al (2007) have reported intercomparison results from a PTR-MS, GC-FID and a commercial DOAS instrument for several days of measurements from an auxiliary monitoring site in Mexico City during the MCMA 2003 field experiment. The comparison showed good agreement, with the exception of benzene measurements by the commercial DOAS, which were greater than the PTR-MS and GC-FID measurements in the early afternoon when ozone levels were high.…”
mentioning
confidence: 99%